The Blockchain: The Next Technological Revolution In The World of The Economy - Abu Farhah, Maher Fuad (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to demonstrates that the world is more inclined to take use of blockchain (BC) systems and their favorable effects on all economic sectors, development, and quality of life enhancement. Because many states already have well-developed industries, government agencies, financial organizations, and educational institutions recognized the need to stay up with the trend and begin planning and preparing for the BC revolution. This paper also identifies 3 realistic examples for Institutions that have rated or made recommendations about this technique "BC". The paper explains how blockchain systems function in practice and why their adoption improves development, innovation, and competitiveness by reducing and simplifying operational procedures. It is one of the most important technical topics in our time, especially with the beginning of the twenty-first century, especially in financial technologies because of the major developments and changes that they have witnessed and their important impact on the global economy. This paper reviews the current academic research on BC, especially in the subject area of business and economics. Based on a systematic review of the literature retrieved, explore the most frequently cited publications, the most economic countries, and the most commonly used keywords. BC technology is the main topic of this paper, which has profound effects in most areas, and the paper aimed to analyze the current application and concept of blockchain systems. The use of block technology generally helps the digital transformation of the economy and promotes transparency. The outputs of this technology are compatible with the rules and regulations of many nations in the sphere of banking and business. It is a tool for improving transparency, decentralization, and security while reducing cost and time. Understanding the processes through which it impacts business and market efficiency will necessitate further academic research.